The line of action of the resultant of two like parallel forces shifts by one-fourth of the distance between the forces when the two forces are interchanged. The ratio of the two forces is : |
1 : 2 2 : 3 3 : 4 3 : 5 |
3 : 5 |
For \(\tau = 0\) \(F_1 (L - x) = F_2 x\) When forces are interchanged we have \(F_2 (\frac{3L}{4} - x) = F_1 (x + \frac{L}{4})\) Dividing the two equations \(\Rightarrow \frac{L - x}{x + \frac{L}{4}} = \frac{x}{\frac{3L}{4} - x}\) \(\frac{3L}{4} = x + \frac{3x}{4} + \frac{x}{4} = 2x\) \(\Rightarrow 3L = 8x\) Substituting the value of x : \(F_1 \frac{5L}{8} = F_2 \frac{3L}{8}\) \(\Rightarrow F_1 : F_2 = 3 : 5\) |